Piratverksemd i nord - nokre døme frå Finnmark tidleg på 1600-talet - Berger, Marie Nystuen (Heimen, 2016)
Source at https://doi.org/10.18261/issn.1894-3195-2016-01-02 Pirates are best known for their impact in southern seas, such as the Caribbean and Mediterranean Seas around the time known as the Golden Age of Piracy from 1690–1730. This article focuses on an area further north, where the history of piracy is less known. In the 1600s, Northern Norway and the northern trading routes to Russia were frequently (or sometimes not) exposed to the threats of pirates and privateers. The trade along the Northern Sea Route must have been tempting for pirates and privateers, especially the long distance trading routes to Arkhangelsk, where merchants traded luxury goods from inland Russia. Through some examples of piratical attacks on local and international merchant shipping outside Vardø and the Russian coast around Kola, the White Sea and Arkhangelsk, the article explores what drew the pirates, where the pirates and/or privateers came from, and how the government dealt with the matter. One important measure to reduce the pirate threat was the use of the Danish-Norwegian navy. The navy had frequent orders to patrol Danish-Norwegian waters to look for possible threats to the Danish crown, such as pirates, merchants without authorization to trade and whale hunters without permission. This is a new research field, where there is still a lot of research to be done before it is possible to say much about the extent to which the pirates attacked these areas and how important the government’s dealings with them were.